(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Marriage is a universal institution and as man developed it became an integral part of human society and as civilization developed it was seen that it influenced all aspects of human life and marriage is no exception to this. India is a diverse religious country which developed a lot in many fields in 77 years of independence. But even today, inter-religious marriage is seen as a stigma in Indian society specifically with the intent of upholding the tenets of religious freedom and safeguarding the fundamental practices of various faiths and beliefs that constitute the country. (Srivastava, 2021)